Study of the Genetic Polymorphisms of ABCB1 3435G>A in Postmenopausal Women Breast Cancer on Paclitaxel Chemotherapy - Mohammed Hasan , Doaa Alaa; Sahib , Ahmed Salih; Al-Rokan, Ahmed Abbas Hasan; Mohsin, Karrar Kadhim (Journal of Contemporary Medical Sciences, 2023)
Objectives: The aim of study was to determine the relationship between this SNPs in postmenopausal women with breast cancer 3435G>A (rs1045642) polymorphism of the ABCB1 gene, and serum concentrations of Paclitaxel chemotherapy in Iraq. Methods: This study included 100 patients (45-75 years) with a clinical diagnosis of breast cancer who were going to start (paclitaxel) chemotherapy. Patients at the oncology center at Imam al-Hussain medical city in Kerbala Iraq, were sorted into groups based on their postmenopausal age, disease duration, and treatment length for this study, which was conducted between July 2022 and October 2022. Serum concentrations of Estradiol and Ca 15.3 were measured in breast cancer patients who had been taking Paclitaxel . Allele-Specific PCR assay determined gene polymorphisms 3435G>A (rs1045642) and HPLC measured paclitaxel drug concentration. Results: The results found There is an inverse relationship between Ca15.3 concentration and patient response to paclitaxel chemotherapy, and when compared to the genotyping frequency of ABCB1 3435G>A (rs1045642) genetic polymorphism, patients with allele AA in their chromosomes respond better (15.56±6.89) than those with alleles GG and GA. Conclusion: After paclitaxel chemotherapy, there were statistically significant differences (p< 0.05) in the reduction of drug concentration among serum patients with the AA genotype for ABCB1 3435G>A (rs1045642).